Sympathetic Responses to Central Hypovolemia: New Insights from Microneurographic Recordings - Ryan, Kathy; Rickards, Caroline A.; Hinojosa-Laborde, Carmen; Cooke, William H.; Convertino, Victor (Frontiers in Physiology, 2012)
Hemorrhage remains a major cause of mortality following traumatic injury in both military and civilian settings. Lower body negative pressure (LBNP) has been used as an experimental model to study the compensatory phase of hemorrhage in conscious humans, as it elicits central hypovolemia like that induced by hemorrhage. One physiological compensatory mechanism that changes during the course of central hypovolemia induced by both LBNP and hemorrhage is a baroreflex-mediated increase in muscle sympathetic nerve activity (MSNA), as assessed with microneurography. The purpose of this review is to describe recent results obtained using microneurography in our laboratory as well as those of others that have revealed new insights into mechanisms underlying compensatory increases in MSNA during progressive reductions in central blood volume and how MSNA is altered at the point of hemodynamic decompensation. We will also review recent work that has compared direct MSNA recordings with noninvasive surrogates of MSNA to determine the appropriateness of using such surrogates in assessing the clinical status of hemorrhaging patients.